Pengaruh Kecerdasan Emosional Terhadap Kinerja Pegawai dengan Kepuasan Kerja sebagai Variabel Intervening - Hamdani; Pentury, Gerrit M.; Maghfirah, Nurul (KAMBOTI: Jurnal Sosial dan Humaniora, 2024)
The Effect of Emotional Intelligence on Employee Performance with Job Satisfaction as an Intervening Variable at the Maluku Province National Narcotics Agency. This research aims to determine the effect of emotional intelligence on employee performance at the Maluku Province National Narcotics Agency with job satisfaction as an intervening variable. This research uses quantitative research methods with questionnaires distributed to the National Narcotics Agency of Maluku Province, totaling 58 people. The technique used in sampling uses saturated sampling or census. The final sample in the study consisted of 43 respondents. The analytical tool used in this research uses SmartPLS version 4.0 analysis with the structural equation modeling or SEM analysis method. The results of this study explain that there is a positive and significant influence between emotional intelligence and employee performance. There is a positive and significant influence between emotional intelligence and job satisfaction. Job satisfaction has a positive and significant influence on employee performance and there is a positive and significant influence of job satisfaction mediating emotional intelligence on employee performance.